STUDY ON CONSUMER ACCEPTANCE OF ICE CREAM CONE WITH ADDITION OF FLOUR SHELL CRAB (Portunus pelagicus) - Rique Prayoga; Suardi Loekman; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research aimed to determine the effect of the as much as addition of crab shell flour (Portunus pelagicus) from the product durability and the level of consumer acceptance. This research was completely randomized design (CRD), with four levels of treatment consisting of ice cream cones that control without the addition of flour shell 0% (C0), addition of shell flour as much as 2.5% (C1), addition of flour shell as much as 5% (C2) and addition of shell flour 7.5% (C3). The experiment was repeated 3 times, so the number of experimental unit in the study was 12 units. The result showed that for was C2 most preferrable by consumer acceptance with 92,50% (74 people) Organoleptic assessment, a sense 91.25% (73 people), the scent 91.25% (73 people) and the texture 92.50% (74 people). For proximate analyser that C2 water content was 3,28%, protein content 12,56%, calcium 9,49 mg and cone resistant to ice cream for 26,7 minutes.Keywords: Cone ice cream, flour, shell crabs, consumer acceptance